MENDETEKSI INDIKASI FINANCIAL STATEMENT FRAUD DENGAN METODE F-SCORE MENGGUNAKAN MODEL FRAUD TRIANGLE - Chasbiandani, Tryas; Azzahra, Fatima; Fujianti, Lailah (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
This research was conducted to analyze the influence of fraud triangle in detecting the effect of fraud triangle in detecting financial statement fraud. The variables in the fraud triangle used are financial stability (ACHANGE), external pressure (LEV) and financial target (ROA) using the F-Score method. The population of this study is manufacturing companies with consumer goods subsectors listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The sample technique used was purposive sampling and obtained 32 companies. This study used panel data regression analysis method and was processed using Eviews 13. The results of this study reveal that external pressure and financial targets have a significant positive effect on financial statement fraud. While financial stability does not affect financial statement fraud